Impact of late gadolinium enhancement extent, location, and pattern on ventricular tachycardia and major adverse cardiac events in patients with ischemic vs. non-ischemic cardiomyopathy - Tat, Emily; Ball, Caroline; Camren, Gerald P.; Wroblewski, Igor; Dajani, Khaled A.; Goldberg, Ari; Kinno, Menhel; Sanagala, Thriveni; Syed, Mushabbar A.; Wilber, David J.; Rabbat, Mark (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Left ventricular late gadolinium enhancement (LGE) by cardiac magnetic resonance (CMR) has been associated with increased risk for life-threatening ventricular tachyarrhythmias. The differences in association between LGE characteristics and prognosis in patients with ischemic (ICM) versus nonischemic (NICM) cardiomyopathy is incompletely understood. Methods: A total of 168 consecutive patients who underwent CMR imaging with either ICM or NICM were included in our study. LGE extent, location and pattern were examined for association to the primary endpoint of ventricular tachycardia (VT) and secondary endpoint of major adverse cardiac events (MACE). Results: Of 68 (41%) patients with ICM and 97 (59%) patients with NICM, median LGE mass was 15% (IQR 9-28) for the ICM group and 10% (IQR 6-15) for the NICM group. On multivariate analysis for both groups, LGE characteristics were prognostic while LVEF was not. In patients with ICM, septal and apical segment LGE, and involvement of multiple walls predicted both endpoints on multivariate analysis. LGE extent (≥median) and inferior wall LGE independently predicted the primary endpoint. In patients with NICM, anterior, inferior and apical segment LGE, and involvement of multiple walls predicted both endpoints on multivariate analysis. LGE extent (≥median, number of LGE segments, LGE stratified per 5% increase) and midwall LGE were independent predictors of the primary endpoint. Conclusions: Although LGE was an independent predictor of prognosis in both groups, LGE extent, location and pattern characteristics were more powerful correlates to worse outcomes in patients with NICM than ICM.